Association between serum-free thyroxine level and all-cause mortality in critically ill patients: a retrospective study from MIMIC-IV - Dai, Juan-Juan; Du, Ding-Fu; Ma, Gang; Jiang, Ming-Jie (Frontiers in Endocrinology, 2023)
Background: Low thyroxine (T4) level has been observed in critically ill patients, however, controversial results regarding T4 supplemental therapy are reported. The association between serum free T4 level and mortality in critically ill patients has not been fully established and needs to be clarified. Methods: Data from the Medical Information Mart for Intensive Care (MIMIC)-IV were collected and analyzed. Association between FT4 level and 30-day mortality after ICU admission was analyzed using Kaplan-Meier curves, spline smoothing fitting, martingale residuals of null cox model and restricted cubic spline (RCS). Logistic regression, Cox regression, receiver operating characteristic curve (ROC) were used to uncover the relation and predictive value of serum FT4 and 30-day mortality in critically ill patients. Results: 888 patients were enrolled in the final analysis, and serum FT4 level was divided into 4 groups. A significant difference in 30-day mortality was observed between the 4 groups. Kaplan-Meier curves also presented significantly higher 30-day mortality in groups 1 and 2 (P < 0.0001). Further multivariance logistic regression showed that group 1 with FT4 level lower than 0.7μg/dL can predict 30-day mortality (OR = 3.30, 95% CI = 1.04-11.31). Spline smoothing fitting analysis showed a “V”-shaped line between 30-day mortality and FT4 level within 0-3 μg/dL. Further RCS analysis showed that risk of death decreased rapidly as FT4 level increased when serum FT4 levels were lower than 1.2 μg/dL, and start to become flat afterwards. The area under ROC of lower FT4 level to predict 30-day mortality was 0.833 (95% CI = 0.788-0.878). Both multivariant Cox regression and logistic regression showed that FT4 level lower than 1.2 μg/dL can independently predict 30-day mortality when adjusted for other potential confounders. (HR = 0.34, 95% CI = 0.14-0.82; OR = 0.21, 95% CI = 0.06-0.79, respectively), but its predictive power disappeared when adjusted for T3 or T4. Conclusion: Serum FT4 level were significantly negatively associated 30-day mortality when it is lower than1.2μg/dL, and can predict the risk of 30-day mortality. Higher FT4 level is potentially related to increased 30-day mortality.